Social Media and the Struggle for Society - Baym, Nancy (Social Media + Society, 2015)
This piece argues that all communication media are inherently social. The term “social media” emerged at the time that companies began harnessing what people were already doing online, turning socializing into revenue streams for venture capitalists and the people who run internet companies. The paper critiques the conversion of social interaction into wealth for the few and argues that we need to fight for media that help build better societies rather than those that view people as data profiles to be sold to advertisers.